Life cycle assessment data structure for building information modelling. (20th October 2018) - Cavalliere, Carmine; Dell'Osso, Guido Raffaele; Pierucci, Alessandra; Iannone, Francesco
Abstract: The assessment of the environmental impacts related to the building lifecycle is a very complex issue because of the high number of variables involved. The aim of the research is to structure the information content into the Building Information Modelling (BIM) framework in order to conduct a Life Cycle Assessment (LCA). An information flows matrix is developed through the investigation of the parameters responsible for the environmental impacts of buildings. Such information content is tested on a case study after implementing the proposed parameters into a BIM. The purpose is to verify that the identified parameters, implemented in the BIM environment, are sufficient to conduct the LCA. The results show that the proposed parameters could potentially improve the data reliability and consistency in the process of sharing information from the digital model to the LCA software. Highlights: A methodology for the integration of LCA and BIM is proposed. The environmental impactful variables over the building lifecycle are identified. The proposed LCA-based parameters are coded for implementing in BIM. Data needed for LCA are made available in BIM and exportable from the model. BIM-LCA integration allows environmental parameters control for decision making.